Problems of Using Texts with Unfamiliar Cultural and Social Context in English Language Learning - Matin, Zakia Noor (Stamford Journal of English, 2013)
Stamford Journal of English; Volume 6; Page 203-218 DOI: http://dx.doi.org/10.3329/sje.v6i0.13914